Chikungunya in Children: A Clinical Review. Issue 7 (July 2018) - Ward, Caleb E.; Chapman, Jennifer I.
Abstract : Abstract: Chikungunya (CHIKV) is an emerging arboviral infection with recent spikes in transmission in the Americas. Chikungunya is most commonly transmitted by mosquitos, specifically Aedes aegypti and Aedes albopictus . These mosquitoes are found throughout many parts of the United States. The classic tetrad of symptoms for CHIKV is fever, symmetric polyarthralgia, maculopapular rash, and nonpurulent conjunctivitis. Although the majority (3 of 4) of infected people will be symptomatic, the viral illness generally runs a benign course. Nevertheless, when compared with infected adults, children more commonly have neurological and dermatological symptoms and are less likely to have arthralgia. The key differential diagnosis to consider is dengue, which has greater immediate morbidity and which can cause coinfection. Local health departments facilitate diagnostic testing, using either RNA polymerase chain reaction or antibody screening based on the timing of presentation. Management is supportive. The purpose of this review article is to provide readers basic knowledge regarding the microbiology, epidemiology, risk factors for transmission, and typical clinical presentation of CHIKV. A practical approach to diagnosis and management of infected children is provided.